Judicial Balancing In Constitutional Law - Hernández , Jorge Edmundo Paspuel; Sandoval, Daniel Vinicio Ruiz; Ordoñez, Paul Esteban Salazar; Gavilanes, Lenin Antonio Tobar (Migration Letters, 2024)
Judicial balancing is a crucial technique in constitutional law, used to resolve conflicts between constitutional principles. This article examines how judges apply balancing when faced with conflicting principles, using a doctrinal, historical and dogmatic methodology. We analyze the historical evolution of the weighting, its doctrinal foundation and the dogmatic interpretation it has received in constitutional jurisprudence. In addition, emblematic cases in various jurisdictions are discussed to illustrate how balancing is applied in judicial practice. The article concludes that, although judicial weighing is essential to guarantee coherence and justice in constitutional interpretation, its application must be carefully calibrated to avoid arbitrariness and ensure respect for fundamental principles.